Analisis Pendekatan Semiotik Terhadap Makna Simbolik dalam Puisi Modern “Lentera dalam Hujan” - Rahel Sinaga (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study aims to analyze the symbolic meaning in the modern poem “Lentera di Dalam Hujan” using a semiotic approach. This approach is employed to reveal the relationship between signs, symbols, and meanings that represent emotional experiences and reflections on life contained in the poem. The method used in this research is a descriptive qualitative method, with the data source being the text of the poem analyzed through the stages of identifying signs, interpreting symbols, and drawing meanings based on semiotic theory. The results indicate that the symbol of the lantern represents hope and inner light, while rain symbolizes sadness, obstacles, and the dynamics of life. Through the relationship between these two symbols, the poem portrays human resilience in maintaining hope amid difficult situations. This study is expected to enrich literary studies, particularly in understanding modern poetry through a semiotic perspective.